Investigation of tick-borne pathogen in goats, case study in Samigaluh, Kulon Progo, Yogyakarta - Yudhi Ratna Nugraheni; Rochmadiyanto; Apinya Arnuphapprasert; Dwi Priyowidodo; Nur Muhamad; Sarwo Edy Wibowo (Jurnal Ilmu Peternakan Terapan, 2023)
Tick-borne pathogens of the genus Theileria and Anaplasma has been widely distributed and infect small ruminant in tropical and subtropical countries. Several species are considered highly pathogenic, while some cause subclinical infections in small ruminants. The distribution data of theileriosis and anaplasmosis in Samigaluh, Kulon Progo remain scarce and poorly understood. Therefore, further investigations are required to control this tick-borne disease. This study aimed to investigate the occurrence of theileriosis and anaplasmosis in domestic goats in Samigaluh, Kulon Progo, Western Yogyakarta. A total of 53 blood samples were collected from domestic goats. Blood sample was drawn from the jugular vein individually and kept in an EDTA tube. Thin blood smear was stained by Giemsa and observed under microscope for genus-level identification. As a result, it was found that theileriosis 12/53 (23%), anaplasmosis 25/53 (47%) and mixed infection 6/53 (11%) were detected in the present study.The conclusion of this study is that the incidence of Anaplasma sp. infection in goats is greater than Theileria sp. infection in Samigaluh, Kulon Progo.Although all domestic goats were asymptomatic, the finding of this study may shed light on the distribution of theileriosis and anaplasmosis infecting domestic goats in Samigaluh, Kulon Progo.